Biocenoses in the loads of iron and manganese removal filters and the methods of settling them in zeolite - Кравченко, Олександр Валерійович (Eastern-European Journal of Enterprise Technologies, 2015)
We have studied the composition of biocenoses in the loads of iron and manganese removal filters and linked the composition to the potency in the processes of iron and manganese removal. We have proved that efficiency of iron and manganese removal is determined by such microorganisms as Leptothrix and Siderocapsa (their ratios are 11-17% and 3-8% respectively) in biocenoses of the loaded filters. We have revealed that effective removal of both elements (up to 92% of iron and 84% of manganese) requires, in addition to the aforementioned microorganisms, equal ratios (2-3%) of Metallogenium, Galionella, Siderocapsa, and Hyphomicrobium in the structure of biocenoses. The devised technique of settling the filters with biocenoses of iron and manganese oxidation microorganisms, which consists in washing the biocenoses off similar filters and settling the wash-offs onto the loads of the new filters. This technique gives a one-day biocenosis almost as active as a twenty-day biocenosis. This peculiarity can be used in technological schemes of iron and manganese removal when dealing with an artificial settlement of microorganisms.